2006
DOI: 10.1149/1.2196026
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inert Anode Materials for Electrowinning in Calcium Chloride Melts

Abstract: The electroreduction of solid titanium dioxide in a calcium chloride melt is an attractive method for the production of titanium metal. Several groups have proposed versions of this route, but no commercial process yet exists. In laboratory studies, consumable carbon anodes are used, and these can give rise to a number of cell design and operational issues. The replacement of the carbon anode with an inert anode offers numerous benefits that include: elimination of carbon dioxide emissions; more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Details of the electrochemical analyses revealed that a growth of 1 μm Si nanowire per unit area is equivalent to 1.56 C charge consumed at a cell voltage of 2.2 V. 65 In a similar direction, Bard et al used the highly conducting Magneĺi phase Ti 4 O 7 as electrode material, 72 which has been previously used for the electroreduction of TiO 2 to elemental Ti. 73 Unlike the carbon anode, where CO 2 is produced during the electrolysis herein with Ti 4 O 7 anode and graphite as the 4). 74…”
Section: ■ Abundance and Application Of Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the electrochemical analyses revealed that a growth of 1 μm Si nanowire per unit area is equivalent to 1.56 C charge consumed at a cell voltage of 2.2 V. 65 In a similar direction, Bard et al used the highly conducting Magneĺi phase Ti 4 O 7 as electrode material, 72 which has been previously used for the electroreduction of TiO 2 to elemental Ti. 73 Unlike the carbon anode, where CO 2 is produced during the electrolysis herein with Ti 4 O 7 anode and graphite as the 4). 74…”
Section: ■ Abundance and Application Of Siliconmentioning
confidence: 99%
“…In a similar direction, Bard et al used the highly conducting Magnéli phase Ti 4 O 7 as electrode material, which has been previously used for the electroreduction of TiO 2 to elemental Ti . Unlike the carbon anode, where CO 2 is produced during the electrolysis herein with Ti 4 O 7 anode and graphite as the cathode in two-electrode cell, only O 2 is liberated with ca.…”
Section: Abundance and Application Of Siliconmentioning
confidence: 99%
“…To reduce environmental impacts and labor, one must find a non‐consumable anode material that is stable in the molten salt with oxygen evolution as the anode reaction . Until now, several types of materials, including oxides and noble metals, have been considered as potential inert anode candidates in molten‐CaCl 2 electrolysis, but none demonstrate the rigorous requirements for practical implementation …”
Section: Introductionmentioning
confidence: 99%
“…This material was first investigated as an anode by McGregor et al. for the electrochemical reduction of titanium oxide to titanium metal in molten CaCl 2 . However, anode deterioration caused by oxidation formed a less conductive layer on the anode surface, limiting the duration of its use to a few hours.…”
Section: Introductionmentioning
confidence: 99%
“…However, the process suffers from low current efficiency due to the occurrence of parasitic side reactions involving the consumable carbon anode. As previously noted, 7 the disadvantages of carbon anodes are as follows:…”
Section: Introductionmentioning
confidence: 99%